If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16z + -24 = (2z + -3) Reorder the terms: -24 + 16z = (2z + -3) Reorder the terms: -24 + 16z = (-3 + 2z) Remove parenthesis around (-3 + 2z) -24 + 16z = -3 + 2z Solving -24 + 16z = -3 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. -24 + 16z + -2z = -3 + 2z + -2z Combine like terms: 16z + -2z = 14z -24 + 14z = -3 + 2z + -2z Combine like terms: 2z + -2z = 0 -24 + 14z = -3 + 0 -24 + 14z = -3 Add '24' to each side of the equation. -24 + 24 + 14z = -3 + 24 Combine like terms: -24 + 24 = 0 0 + 14z = -3 + 24 14z = -3 + 24 Combine like terms: -3 + 24 = 21 14z = 21 Divide each side by '14'. z = 1.5 Simplifying z = 1.5
| 3x-1+x(-3)= | | 3z+14=2x+14 | | .25r+9=10-.75r | | -7x+35=7x-35 | | 0.12x=0.6 | | 225=10(x-65)+75 | | 0.7h=-0.112 | | 5x-7=2x+33 | | f(-3)=x^2+3 | | 2x-5y=-23 | | 1600x=950x+211,250 | | 5x-17=180 | | 1600x=950+211,250 | | -12f=-180 | | 7x-(12)=3x | | -13a=52 | | 3x=7x-(12) | | z-8z=9z-1-z | | 0=x^4+16x^2-36 | | 9b-10=(-b)-18 | | -10x+14-3x=-12 | | 60t=45(t+1) | | 8f+11=-7f-(19) | | 2y^2+2y-24=0 | | -(6x-12)= | | -9=3x-17 | | x^6+x= | | 5z-(43)=2z+80 | | 21x^2-18x-20=0 | | -4x+5y=-35 | | 16x+8=24 | | 10x-3=2x+21 |